Small and medium enterprises pursuing organizational excellence: a toolkit for improvement - Correia, Fábio (2020)
Purpose - This paper presents the development of a new organizational excellence tool specifically for use by small and medium-sized enterprises (SME) while implementing business excellence models. A literature review was conducted to analyse the current state of business excellence models and their content and application around the world, including the identification of key principles that drive their creation and implementation. In this paper, we present a framework that has been validated by an Expert Panel of Organizational Excellence Professionals, considering the unique characteristics of SME and their industry contexts. It is hoped that this toolkit will allow these companies to strive for organizational excellence through a framework that is better suited to their context and needs. Design/methodology/approach - An initial extensive literature review was conducted on the topics of Excellence Frameworks, Excellence Programs, Excellence Awards and the different contextual environments between LE and SME. Based on the literature review, we began by reviewing several scientific articles aimed at understanding the different contexts of LE and SME. From this point of view, and with a focus on small and medium-sized enterprises, we emphasized the themes that offered a better fit to the needs of these organizations and that, as a result, should be integrated into this framework. The Quality and Organizational Excellence Framework for Small and Medium Enterprises (QOE-SME) was built based on the weaknesses and shortcomings found in the use and implementation of SME's excellence models. The model was then validated by a group of quality experts through an online survey. This group was chosen based on criteria for reaching out to people who, in both academia and industry, have carried out significant and appropriate research in the field of organizational excellence and/or in the field of quality promotion and superior performance in SME. Findings - Organizational excellence programs have created a catalyst and frameworks for improved success and productivity within large organisations. However, small and medium-sized organizations often try to achieve the same results using these same structures. However, evidence suggests that some of these frameworks are seen as unrealistic and difficult to implement. These implementation levels and records of positive implementation of OE models in SME are still small. The question is seen by both practitioners and researchers because of the various implementation difficulties faced by SME. Such perceived difficulties contributed to the development of the QOE-SME Framework.